Development and verification of a constitutive model for human periodontal ligament based on finite element analysis. Issue 9 (4th July 2022) - Wu, Jianlei; Liu, Yunfeng; Li, Boxiu; Dong, Xingtao
Abstract: This study aimed to develop a constitutive model for human periodontal ligament (PDL) by combining the hyperelastic and viscosity models. We performed the finite element analysis (FEA) to simulate the experimental processes of the PDL in vitro and in vivo tests to verify the developed model. The FEA results indicated that the simulative curves were consistent with the experimental curves in the PDL in vitro tests. Moreover, for the in vivo measurements, the simulative result of 0.6258 N was similar to the experimental value of 0.65 N. The study results can help orthodontists better understand the biomechanical characteristics of PDL.